PENDEKATAN NORMATIF DALAM STUDI HUKUM ISLAM - M. Mohsi (HKI IAI Miftahul Ulum Pamekasan, 2020)
Like other religions, Islam has two dimensions that cannot be separated, namely the esoteric dimension in which Islam transcends space and time, transcends rationality, is transindent and absolute. And secondly, it has an exoteric dimension, this is religion exists in a structured form, exists in space and time, rationality, is limited and relative. With these two dimensions, Islam is able to provide wide space for its adherents to always carry out research and stabilization through good understanding with one of the goals of restoring all Islamic traditions that are maintained even though the dynamics of the times are very rapid. Keywords: Normative Approach, Islamic Law Studies